AOAC-OMA/MicroVal Harmonized Validation of Peel PlateTM EB (Enterobacteriaceae Bacteria), First Action 2018.05. (17th June 2020) - Salter, Robert S; Durbin, Gregory W; Martinez, Denisse; Bird, Patrick; Bastin, Benjamin; Crowley, Erin
Abstract: Background: Peel Plate TM Enterobacteriaceae Bacteria (EB) is dried selective media on a 47 mm plastic plate that produces enzyme substrate colored colonies on rehydration and incubation for 24 h and up to 48 h at 37 ± 1°C. Purpose: The method validation compared quantification of EB to reference methods ISO 21528:2017 Parts 1 and 2. Methods: Matrixes compared were whole milk, skim powdered milk, vanilla ice cream, butter, infant formulas (soy- and dairy-based), infant cereals ± probiotic, environmental sponge swab of stainless steel surface, and poultry carcass rinse with two different peptone buffers. Results: In inclusivity and exclusivity studies, the method detected 54 of 54 EB strains and did not detect 30 of 30 non-EB strains. In matrix studies, the claimed foods were tested at three contamination levels using paired analysis between the reference and Peel Plate EB methods. Colony-forming units per gram or mL [CFU/g (mL)] were log10 transformed for statistical analysis. The candidate method and reference method were shown to be equivalent by the performance requirement of all 95% confidence intervals on mean difference falling between −0.5 and +0.5 log10 CFU/g (mL). An international collaborative study with dried infant formula spiked with Cronobacter sakazakii at log10 CFU/g (mL) 1.05, 2.31, and 3.21 levels, produced method differences −0.16, 0.15, and 0.18 log10 CFU/g (mL) with repeatabilities ( r ) = 0.33, 0.20, and 0.12 log10 CFU/g (mL) and reproducibilities ( R ) = 0.45, 0.26, and 0.18 log10 CFU/g (mL). Conclusions: Based on these evaluations, the candidate method is considered equivalent to the reference methods at both the 24 h and 48 h incubation periods at 37 ± 1°C. Highlights: Ready to use Enterobacteriaceae method equivalent to ISO-21528:2017 Parts 1 and 2; EB test colored colonies at 37°C for 24 h are equivalent at 48 h incubation; Singlet determined CFU/mL are statistically the same as duplicate average results; EB test validated for infant formula and dairy products including with probiotics; EB test for environmental surfaces and poultry carcass rinses using peptone buffers.